Perbandingan Metode Membran Filter dan Metode Tabung Ganda Terhadap Kandungan Escherichia coli pada Air Bersih - Lathifa Azkhiyati; Dheasy Herawati; Setyo Dwi Santoso; Esti Rizkiana Pratiwi; Elsa Mega Suryani (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2023)
Escherichia coli bacteria are bacteria used as indicators of contamination. Bacteriological water testing can use a Membrane Filtration (MF) and a Multiple Tube-Fermentation (MTF). This study aims to compare the membrane filtration and Multiple Tube-Fermentation methods on the presence of Escherichia coli in clean water. The two methods are compared to determine the percentage difference in the results of the two tests. The research methodology uses a description of observation. 20 samples of water boreholes were used and tested for the presence of Escherichia coli. Calculation of bacterial groups uses SNI standard references regulated by the Minister of Health of the Republic of Indonesia. The results showed that the average number of Â Escherichia coli bacteria by the Multiple Tube-Fermentation method was less than the Membrane Filtration method. There is a difference in the percentage of the results of the two tests by 40%. Multiple Tube Fermentation is more sensitive than the Membrane Filtration method for detecting the presence of Escherichia coli in clean water.Keywords : Water, Escherichia coli, Membrane filtration, Multiple tube-fermentation